Big Nate : this means war! - Peirce, Lincoln (Peirce, Lincoln. Big Nate ;, 2024)
"For Nate Wright, conflict is a way of life. He tangles with Gina, the editor of the school newspaper, after she rejects his comic strip. He can't get on the same page with his snooty study partners as they cram for the final exam. And once he hears that Mr. Rosa's job is on the line, Nate even takes on the all-powerful school board. But when a challenger threatens Nate's status as the owner of P.S. 38's filthiest locker, our hero may have met his match. Can he win the slob-off and bury Kyle under the ash heap of history? In this brand-new collection of comics, Nate is definitely NOT messing around."--